Analysis of The Micro Pile Casting Method Using The Jet Grouting Method in The RDMP JO Balikpapan Project - Kuncoro, Dwi Wahyu; Ade Jaya Saputra (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
The increase in foundation bearing capacity is crucial for the RDMP project, which is a National Strategic Project in Indonesia. This study analyzes the casting of micro pile foundations using the Jet Grouting method, an alternative grouting technique used to enhance foundation bearing capacity. The research involves site selection, planning, implementation of Jet Grouting, and analysis of foundation bearing capacity using the Mayerhoff method and Standard Penetration Test (SPT) data. This method injects high-pressure grouting material into the ground, forming solid columns that support refinery infrastructure and improve the soil strength around the foundation. The results show an increase in foundation bearing capacity and soil strength, with Mayerhoff method results of 6,200.08 kN and SPT results of 3,476.98 kN. In conclusion, Jet Grouting successfully improves foundation bearing capacity and becomes an innovative and effective method for geotechnical challenges in specific projects, providing new insights for construction practitioners on optimizing foundation bearing capacity in the RDMP project.